Hybrid aortic arch repair - Czerny, Martin; Schmidli, Jürg; Carrel, Thierry; Grimm, Michael (Annals of Cardiothoracic Surgery; Vol 2, No 3 (May 30, 2013): Aortic arch surgery (II), 2013)
The successes of thoracic endovascular aortic repair (TEVAR) have spurned new approaches to addressing thoracic aortic pathologies. These hybrid techniques offer an alternative in patients with multi-segmental thoracic aortic pathologies which would have otherwise required a two-step arch replacement and open descending arch repair. The following article offers a clinical insight to the available hybrid approaches, such as rerouting of supra-aortic vessels. Unique complications to endovascular repairs, and technical risks and issues, are also presented along with management options and strategies to minimize such concerns.